Phosphorus and Amylose Branching in Rice Starch Granules - Hizukuri, S.; Shirasaka, K.; Juliano, Bienvenido O. (Wiley, 1983)
Phosphorus content of rice starch granules prepared by DoBS extraction of milled rice protein was lowest and was mainly 6‐phosphoglucose for 2 waxy rices. For 6 nonwaxy rices it was highest and predominantly phospholipid P based on choline content. Defatting with water‐saturated butanol reduced both choline and P content of nonwaxy rice starch. Once recrystallized amylose of 7 rices had 72–84% β‐amylolysis limit, DP 532–793 glucose units per reducing end, CL 101–157 glucose units per nonreducing end and 3.4–7.5 branches/molecule.